Predicting platinum-resistance in advanced ovarian cancer: defining patient and disease characteristics to improve treatment approaches at initiation of treatment or earlier in the course of the disease - Chase, Dana M.; Patton, Gregory; Annavarapu, Srinivas; Shi, Junxin; Szamreta, Elizabeth; Monberg, Matthew (Frontiers in Oncology, 2026)
IntroductionThis study aimed to describe differences in characteristics and outcomes between patients with platinum sensitive or platinum resistant advanced ovarian cancer in a community oncology setting.MethodsThis was a retrospective study of adult patients with Stage III/IV ovarian cancer who received 4+ cycles of a front-line platinum-based regimen between 01/01/2017 and 06/30/2021 (followed until 12/31/2021) within The US Oncology Network. Platinum sensitive or resistant patients were included while refractory patients were excluded. Structured and chart review data were used. Multivariable logistic regression assessed factors associated with platinum sensitivity vs. resistance.ResultsA total of 108 platinum sensitive and 34 resistant patient charts were reviewed. In addition to platinum-based chemotherapy, 19% of patients also initiated bevacizumab as part of their front-line regimen. Most patients were White (63%) and diagnosed at Stage IIIC (55%) or IV (33%). ECOG performance status scores were 0/1 for 47% and 2+ for 20% of patients while BRCA mutations were observed among 7.7%. Sensitive vs. resistant patients were younger (p=0.045) and fewer were obese (p=0.011). Stage IV disease (odds ratio [OR]=3.6, p=0.009) was associated with significantly higher odds of platinum resistance after front-line treatment compared to Stage III, while obesity (OR = 2.6, p=0.067) and ECOG 2+ (OR = 2.9, p=0.057) were non-significantly associated with higher odds of resistance. Median overall survival was not reached in sensitive patients, and was 16.7 months in resistant patients. Median progression-free survival in sensitive and resistant patients was 19.6 and 7.9 months, respectively.DiscussionWhen exploring factors associated with response to front-line platinum-based treatment of ovarian cancer, Stage IV disease was significantly associated with resistance. As platinum resistant patients have poorer survival and fewer treatment options, it is important to further define the biology and appropriate initial management of these patients.